Intermittant antibiotics vs. continuous antibiotics for the finishing pig - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1981)
The use of low or high level antibiotics fed continuously or intermittantly (2 week rotation) to 310 finishing pigs was evaluated in two trials. No significant improvements were noted for rate of gain or feed per lb. of gain in pigs fed antibiotics either continuously or intermittantly, as compared with pigs fed no antibiotics. No difference in performance was observed in pigs fed antibiotics intermittantly or continuously. The rotation of two high level antibiotics in Trial II did not significantly improve the performance of pigs over that of pigs fed no antibiotics.; Swine Day, Manhattan, KS, November 12, 1981
Keywords: Swine day; 1981; Kansas Agricultural Experiment Station contribution; no. 82-128-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 406; Swine; Intermittant antibiotics; Continuous antibiotics; Finishing pigs